Comparison of the Techniques of Secondary Intraocular Lens Implantation after Penetrating Keratoplasty. (12th September 2018) - Krysik, Katarzyna; Dobrowolski, Dariusz; Wroblewska-Czajka, Ewa; Lyssek-Boron, Anita; Wylegala, Edward
Abstract : Aim . To conduct a retrospective analysis of secondary IOL implantation in patients who underwent PK with no simultaneous IOL implantation. Materials and Methods . The retrospective study of the secondary implantation of IOLs was conducted in 46 eyes that underwent a primary operation with PK and cataract/lens extraction with no IOL implantation due to capsule rupture or combining corneal or intraocular complications. The minimum period from PK was 12 months. All secondary IOL implantations were performed from January 2011 to August 2017. Aphakic postkeratoplasty patients were treated using one of the surgical techniques for secondary IOL implantation. In-the-bag IOL implantation was possible if the posterior capsule was complete. If the lens capsule remnants were sufficient to provide secure IOL support, an in-the-sulcus IOL implantation was performed. Scleral fixation was offered in eyes with extensive capsular deficiency or the presence of the vitreous body in anterior chamber. BCVA and expected and achieved refraction were evaluated; we included using two biometry devices, and results were compared. Results . The corrected distance visual acuity (CDVA) before surgery ranged from 0.1 to 0.8 (mean 0.54 ± 0.17). After secondary IOL implantation, CDVA ranged from 0.2 to 0.8 (mean 0.43 ± 0.14) at postoperative 1 month and from 0.3 to 0.9 (mean 0.55 ± 0.15) at postoperative 6 months (p < 0.05 ). Comparison of the final refraction using two methods of biometry showed no statistically significant difference in the group that underwent scleral fixation of the IOL, similar to the findings for the in-the-bag and in-the-sulcus IOL implantation groups. In the scleral-fixation group, p = 0.55 for the USG biometry technique andp = 0.22 for the OB technique.p values for the IOL-implantation group werep = 0.49 andp = 0.44, respectively. Conclusion . Both implantation methods are safe for the patients. Final refraction is depending on the technique and indication to keratoplasty. Both biometry techniques deliver precise data for IOL choice.